Cases on innovative and successful uses of digital resources for online learning - Lantz, Jessica L.; Sullivan, Brian A.; Sullivan, Pamela M. (IGI Global, 2022)
"The goal of this reference book is to evaluate and describe successful initiatives in remote and hybrid learning during the pandemic disruption to traditional schooling for early childhood through college and job training levels, promoting digital-based project learning and facilitate engagement in the curriculum